ANALYSIS OF PB CONTENTIN THE WATER AND Notopterus notopterusOBTAINED FROM THE SAIL RIVER, PEKANBARU RIAU PROVINCE - Muhammad Arib Faishal; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractFish that live in the area that is polluted by heavy metal such as Pb may accumulate that metal in their body.To understand the Pb content in the water and in theN. notopterusobtained from theSail river, a research has been conducted in February 2018. There were 3 stations, in the upstream (St I), in the middle area of the river (St II) and in the downstream (St III). Samplings were conducted 3 times, once/ 5 days. Resultsshown that the concentration of Pb in the water were 1.09 mg/L (St I), 3.09 mg/L (St II) and 2.90 mg/L (St III). Concentration of Pb in the N. notopterusmeat were 0.49 mg/Kg(St I), 0.56 mg/Kg(St II) and 0.52 mg/Kg(St III).The highest concentration of Pb in the water as well as in the fish was obtained in the St II, indicating that the environmental condition of St II was worse than other areas.Based on the Pb concentration in the water and in the meat of N. notopterus, it can be concluded that the Pb concentration in the water of the Sail River is dangerous for aquatic organisms living in that river and N. notopterusfrom that river is unsafe for being consumed.Keywords :fish consumption, heavy metal, lead, clown knifefish.